Zhongguo feng jian she hui. - Qu, Tongzu, author.
1 online resource.
Keywords: "Feudalism is one of the most studied topics in the field of history but without a consensus on its central characteristics, it remains a slippery concept. The History of Chinese Feudal Society provides a comprehensive analysis on the rise and fall of feudalism in China. Drawing on a vast resource of archival materials, it is the first study to investigate feudalism in China from the perspective of sociology and to compare feudalism in China to feudalism in the West. The author proposes that land ownership and the relationship between land owners and farmers are the two determining factors of feudalism with the Yin Dynasty marking a transitional stage to feudalism while the Zhou Dynasty saw the establishment of feudalism as a political system and central institution. This book was written by one of the best-known Chinese historians and has been a classic best-seller for decades. Students and scholars of Chinese history, especially Chinese feudalism, will find it to be an essential reference in their study and research"--